Differences in improving learning outcomes and student learning motivation - S. Sudirman; Kms. Muhammad Amin Fauzi; Anita Yus (Inovasi Kurikulum)
The Mathematics Learning Grade IV at SD Negeri 1 Syamtalira Bayu has yet to reach the indicators. Ideally, learning mastery occurs when 76% of students score above the Kriteria Ketuntasan Minimal (KKM). This study aims to determine the differences in students' learning outcomes and motivation through teaching using the Contextual Teaching and Learning (CTL) and discovery learning models. This quasi-experimental study involved two Grade IV-B and IV-A classes as the research sample. The research instruments used were tests and a motivation questionnaire. Data analysis was conducted using t-test and N-Gain analysis. Based on the results of the analysis, it was found that students' learning outcomes using the CTL model were higher than those using the discovery learning model. The learning motivation of students in the CTL model class was higher than in the discovery learning model class. Based on the research, the CTL model can improve students' learning outcomes and motivation.